STEAM Education in Nepal: Status, Opportunities, Challenges and Future Perspectives for Nurturing 21st Century Learners - Pant, Binod Prasad; Dahal, Niroj; Luitel, Bal Chandra; Shrestha, Indra Mani; Manandhar, Netra Kumar; Rajbanshi, Roshani; Dhungana, Parbati; Luitel, Laxman (Mathematics Education Forum Chitwan, 2024)
STEAM Education is an innovative approach to learning that integrates science, technology, engineering, arts/humanities, and mathematics. STEAM education is gaining popularity these days in the educational field as one of the alternative modes of nurturing students to produce critical and creative human citizens. STEAM approaches have been in practice in Nepal since 2014. In this article, we explored the status, opportunities, challenges, and future perspectives of STEAM education for nurturing 21st-century learners. Likewise, STEAM approaches have been implemented by different organizations in Nepal based on the integrated curriculum of the basic schools of Nepal. The newly developed basic school curriculum at the school and the programs run by the Kathmandu University School of Education are the foundation of STEAM Education. This argumentative article subscribed to the conceptual framework of co-generative inquiry in writing, as articulated by Luitel and Taylor (2007), to foster innovative educational insights aligned to the status, opportunities, challenges, and future perspectives of STEAM education. The article highlights opportunities at different levels: innovation in pedagogy, art-integrated learning, integrated projects, and responsible citizens. At the same time, several challenges, starting from the mindset of people, the footprint of conventional pedagogical approaches, and the influence of positivist ideas in the curriculum and assessment system on the overall culture of education, also got the room for discussion, offering the future perspectives of STEAM education. This argumentative article aims to critically analyze the present situation and envisage possible ways to carry on. In doing so, the argumentation was made from the perspective of transformative STEAM Education and transformative learning. This article is useful for teachers, teacher educators, researchers, and policymakers who aim to understand the present status of STEAM Education in Nepal and aim to advocate from their own places for the betterment of the education system of Nepal.